The Interpersonal Mattering Scale: its reliability and validity in an Iranian sample. Issue 3 (16th March 2021) - Dadfar, Mahboubeh; Lester, David; Sanadgol, Siyamak
ABSTRACT: Mattering is a social-psychological, emotional and cognitive concept related to the sense of belonging to and with others, thereby reducing the sense of isolation and reducing the lack of communication within the social context. The aims of the present study were: (a) to investigate the psychometric properties of the Interpersonal Mattering Scale (IMS), (b) to explore correlations between mattering and happiness, psychological well-being and loneliness, (c) to explore sex differences, and (d) to compare staff with a clinical sample. A sample of 72 Iranian university staff was recruited from the Iran University of Medical Sciences. They responded to the Farsi versions of the IMS, Self-Rating Scale of Happiness (SRH), World Health Organization-five Well-Being Index (WHO-5), and Loneliness Scale (LS). A Principal Component Analysis (PCA) extracted eight factors (72.94% of the total variance), indicating great heterogeneity in the item content. Cronbach's a was .68 for the IMS, .46, .50, and .47 for its three elements, respectively. None the correlations between mattering and happiness, well-being and loneliness were statistically significant. There were no sex difference in IMS scores. The university staff had lower mattering scores than did the psychiatric outpatients. These results indicated that the IMS is heterogeneous in content and that mattering may not be useful for predicting happiness, psychological well-being, and loneliness in Iranian employees.